Human factors and safety culture: Challenges and opportunities for the port environment. (November 2019) - Corrigan, S.; Kay, A.; Ryan, M.; Ward, M.E.; Brazil, B.
Highlights: One of few empirical studies focusing on HF and Safety Culture in the port environment. The application of methodological approach that has been validated in applied industrial research. The application of the Safety Cultural Maturity Model. A solid platform for future research in this 'under-researched' area. Recommendations for steps ports need to consider to move to a resilient safety culture. Abstract: The critical role of understanding Human Factors and the importance of Safety Culture in the maritime sector is becoming much more topical. While the key focus of much of the research in this sector has been on seagoing vessels, it is also important to recognise that ports and docks can be particularly dangerous and hazardous environments. The objective of this paper is to report on an exploratory research study assessing the safety culture and human factor awareness in a large European port environment. The research study adopted a multi-methods approach that included the completion of a Safety Culture Assessment Survey across a port environment (161 responses) and research interviews (11 in total) with a port authority company. The research concludes that there is an increasing awareness of human factors and a move towards a positive safety culture that facilitates an open and resilient approach to all safety practices. However much more focused research is required focusing on the specific complexities, constraints and shared processes of our port environments.